Cognition and hypocognition: Discursive and simulation-supported decision-making within complex systems. (April 2023) - Polhill, J. Gareth; Edmonds, Bruce
Abstract: Homo sapiens is currently believed to have evolved in the African savannah several hundreds of thousands of years ago. Since then, human societies have become, through technological innovation and application, powerful influencers of the planet's ecological, hydrological and meteorological systems – for good and ill. They have experimented with many different systems of governance, in order to manage their societies and the environments they inhabit – using computer simulations as a tool to help make decisions concerning highly complex systems, is only the most recent of these. In questioning whether, when and how computer simulations should play a role in determining decision-making in these systems of governance, it is also worth reflecting on whether, when and how humans, or groups of humans, have the capability to make such decisions without the aid of such technology. This paper looks at and compares the characteristics of natural language-based and simulation-based decision-making. We argue that computational tools for decision-making can and should be complementary to natural language discourse approaches, but that this requires that both systems are used with their limitations in mind. All tools and approaches – physical, social and mental – have dangers when used inappropriately, but it seems unlikely humankind can survive without them. The challenge is how to do so. Highlights: Making policy decisions in complex and wicked systems is, we argue, beyond the limits of individual or collective cognition. We contrast the use of simulation with divination and discursive approaches to decision-making. We posit an 'ecocyborged' future in which computation is embedded in the dynamics of social-(technical-)ecosystems. We recommend an open science approach to the use of simulations in policy-making. We note that discursive and simulation approaches to decision-making should complement, not exclude each other.